Capital Market Reaction to Several Announcements Related to COVID-19 Vaccine in LQ-45 Index - Johan, Suwinto; Victoria, Erika (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2022)
COVID-19 has caused many losses to stock markets worldwide, including in Indonesia. All industrial sectors' stock prices have declined significantly from December 2019 to May 2020. Due to the pandemic, the COVID-19 vaccine brings hope and optimism to the country's economy, which will cause a reaction in the capital market. This study aims to test is there any market reaction to several cases related to the COVID-19 vaccine. Those events are: the government received the first dose Covid-19 vaccine, the government canceled the paid individual vaccination program, and COVID-19 vaccination has penetrated more than 100 million people. This study was measured by abnormal return and trading volume activity within two different periods, i.e., a day before (D-1) to a day after (t-1) and three days before (t-3) to three days after (t+3) of each event. This research was conducted on companies listed on LQ-45 that were determined using the purposive sampling technique and will be analyzed using a one-sample Kolmogorov Smirnov test, Paired sample t-test, and Wilcoxon signed-rank test. This study indicates a capital market reaction to all the cases related to the COVID-19 vaccine researched in this study, which causes changes in abnormal returns and a significant increase in volume after the announcement.